PENGARUH KEUANGAN DAERAH TERHADAP PERTUMBUHAN EKONOMI KOTA PEMATANG SIANTAR - Toga Sehat Sihite; Darwin Damanik (POLITEKNIK LP3I JAKARTA, 2022)
This study aims to determine whether regional finance, namely PAD, DAU, and DAK have a significant effect on economic growth in Pematang Siantar City. The type of research used is quantitative and descriptive research. The type of data used in this study is in the form of a time series from 2006 - 2021 which is secondary data sourced from BPS Siantar City. The analysis technique uses Multiple Linear Regression (OLS) with the help of the EVIEWS 10 Program. The results of the study show that: 1). Regional Original Income (PAD) has a positive and significant effect on economic growth in Pematangsiantar City; 2). The Special Allocation Fund (DAK) has a negative and insignificant effect on economic growth in Pematangsiantar City; 3). The General Allocation Fund (DAU) has a positive but not significant effect on economic growth in Pematangsiantar City; 4). The coefficient of determination (R2) of 0.845, which means that the PAD, DAK, and DAU variables have an explanatory variation of 84.50 percent of the economic growth of Pematang Siantar City, the remaining 15.50 percent can be explained by other variables.Key words: Local Own Revenue, Special Allocation Fund, General Allocation Fund